Analisis Profil Beban Dinamis dan Kestabilan Tegangan pada Sistem Traksi Listrik Kereta Berbasis Inverter VVVF di Perusahaan Manufaktur Kereta Api - Jannah, Qalqiliya Raudhatul; Kusban, Muhammad (Lembaga Teewan Journal Solutions, 2026)
Electric railway traction systems experience dynamic load variations during acceleration, cruising, braking, and idle operation, leading to fluctuations in current and voltage, particularly at the input of the Variable Voltage Variable Frequency (VVVF) inverter. These fluctuations may affect traction system performance, especially voltage stability under rapid load changes. This study analyzes the onboard traction system using real operational data, including VVVF output current, input voltage, train operating conditions, and timestamps. The analysis is limited to the onboard traction system and excludes traction substations and the external power distribution network. Statistical parameters, including average, minimum, and maximum voltage, standard deviation, and voltage drop percentage, were calculated to compare normal and fault conditions. The results indicate that fault conditions are characterized by a significant decrease in minimum voltage (from 933.11 V to 8.50 V), an increase in average current (from 37.80 A to 50.57 A), higher dynamic loading, and a greater voltage drop (from 2.64% to 5.34%), while the average voltage remains relatively stable. These findings demonstrate that voltage drop and current characteristics are effective indicators for evaluating traction system performance under varying operating conditions.